Applications of artificial intelligence in supply chain management: Identification of main research fields and greatest industry interests - Sandra Lechtenberg; Bernd Hellingrath (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2021)
Advances in the area of computing power, data storage capabilities, etc., are changing the way business is done, particularly regarding how businesses use and apply artificial intelligence. To better understand how artificial intelligence is used in supply chain management, this paper identifies and compares the main research fields investigating this topic as well as the primary industry interests in it. For this, we performed a structured literature review that shows which methods of artificial intelligence are applied to which problems of supply chain management in the scientific literature. Then, we present industry-driven applications to provide an overview of fields that are most relevant to industry. Based on these results, indications for future research are derived.
Keywords: 650; artificial intelligence; supply chain management; logistics; applications; industry-driven